2021
DOI: 10.26451/abc.08.04.06.2021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Visitor Presence and Crowd Size on Zoo-Housed Red Kangaroos (Macropus Rufus) During and After a COVID-19 Closure

Abstract: Macropods, particularly kangaroos and wallabies, are common species included in walk-through habitats that put them in close proximity to zoo visitors. However, there has been little research into how visitor presence and density impact the welfare of these individuals. We monitored the behavior and space use of fifteen red kangaroos (Macropus rufus) for a total of ten weeks during and after a nearly three-month zoo closure due to the COVID-19 pandemic. Our findings revealed potential visitor effects, evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 43 publications
(69 reference statements)
0
18
0
Order By: Relevance
“…Anecdotal reports from zoological facilities during COVID-19 lockdown periods highlighted the fact that primates were looking out for keepers [55], and so these individuals could have been responding to the increased stimulation when visitors returned. It is, however, important to bear in mind that the time frame over which these data were captured was relatively short, so it is possible that the gorillas, as has been reported in other species [26,56], were taking longer than the bonobos or chimpanzees to rehabituate to zoo visitors when facilities reopened.…”
Section: Behavioural Changesmentioning
confidence: 99%
See 2 more Smart Citations
“…Anecdotal reports from zoological facilities during COVID-19 lockdown periods highlighted the fact that primates were looking out for keepers [55], and so these individuals could have been responding to the increased stimulation when visitors returned. It is, however, important to bear in mind that the time frame over which these data were captured was relatively short, so it is possible that the gorillas, as has been reported in other species [26,56], were taking longer than the bonobos or chimpanzees to rehabituate to zoo visitors when facilities reopened.…”
Section: Behavioural Changesmentioning
confidence: 99%
“…Avoidance behaviours have been known to increase in response to increased visitor number and noise levels at enclosures for orangutans [61], and a number of studies have reported gorillas turning their back on enclosure windows (another behaviour indicative of public avoidance) in relation to increased visitor presence [62,63]. Strategic use of enclosures to avoid human-animal interactions has also been reported in animals in petting zoos [63], and changes in enclosure usage/visibility of animals following periods of closure during the COVID-19 pandemic have also been reported in red kangaroos [26], Grevy's zebra (Equus grevyi) [56], and tokay geckos (Gekko gecko) [64]. The short-term behavioural modification in terms of altered space use may therefore represent a coping mechanism that the gorillas in this study employed when the zoo was open to the public.…”
Section: Enclosure Use: Impacts Of Enclosure Design and Visitor Numbersmentioning
confidence: 99%
See 1 more Smart Citation
“…Most visitor-based researchers have investigated the effects of crowd size [11,14,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], length of time at the enclosure [23,29,30,33], zoo attendance [12,17,28,[34][35][36][37][38][39], visitor attendance days [8,9,40,41], observer effects [42], and visitor attendance times [16] on animal behavior. Additionally, visitor behavior [6,20,23,29,31,33,[43][44][45], including noise levels [6,11,18,…”
Section: Introductionmentioning
confidence: 99%
“…The initial wave of the SARS-CoV-2 (COVID-19) pandemic in early 2020 forced zoos to close for the first prolonged period of time in the United States (U.S.) and globally. Since then, several visitor effect studies of various zoo-housed taxa have been published due to the unique opportunity these closures provided [17,[25][26][27][49][50][51][52][53]. Greater flamingos (Phoenicopterus roseus) showed no behavioral changes between the open and closed conditions, while Chilean flamingos (P. chilensis) showed a decrease in three out of eight observed behaviors (activity, movement, and feeding) when the zoo reopened; however, these changes were partially attributed to weather [27].…”
Section: Introductionmentioning
confidence: 99%